Covid-19: Mitigation Approach towards Pandemic - Bharti, Aditi; Sharma, Arvind (National Journal of Community Medicine, 2020)
The COVID-19 pandemic affected all layers of the population in the world. It has been spreading all over the world rapidly. In a large country like India, elimination may be achieved locally, but in every area, it may be daunting. Control measures would be attained by administering the actions to attenuate the infectious source, transmission route, and susceptible population epidemiologically. It could be possible in the collaboration of the following "approach" which potentially will turn out to be a hindrance to the spread of COVID-19 to combat the challenge of diminishing this pandemic.